Catalytic asymmetric synthesis of acyclic arrays by tandem 1,4-addition-aldol reactions. - Howell, G; Fletcher, S; Geurts, K; ter Horst, B; Feringa, B (2006)
Herein, we report efficient acyclic stereocontrol in tandem 1,4-addition-aldol reactions triggered by catalytic asymmetric organometallic addition. Grignard reagents add to alpha,beta-unsaturated thioesters in a 1,4-fashion and the resulting magnesium enolates are trapped with aromatic or aliphatic aldehydes. The process provides a range of tandem products bearing three contiguous stereocenters with excellent control of relative and absolute stereochemistry. The various diastereomeric products have been fully characterized using single-crystal X-ray analysis and the origins of stereocontrol in this tandem protocol are discussed. The versatility and efficiency of this methodology are demonstrated in the first catalytic asymmetric synthesis of (-)-phaseolinic acid with 54% overall yield via a short and concise route.